High-wear-resistance cement tile and preparation method thereof

By using cement and wear-resistant fillers of specific ratios, combined with graphene modification and spray maintenance technology, high wear-resistant cement tiles are prepared, which solves the problem of cracking and damage of existing cement tiles and achieves a higher level of Hardness and wear resistance.

CN119462017AActive Publication Date: 2025-02-18XIAMEN TEFANG CONSTR ENG GRP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411652681.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Existing cement tiles are prone to cracks and wear, and it is difficult to meet the market's requirements for improving their wear resistance and decorative effects.

Method used

Use white cement, ordinary cement, wear-resistant fillers, oxidized pigments, quartz sand, fine sand, fine aggregate and sodium feldspar to obtain materials through material preparation, molding, grouting, mold extraction, screening and brick pressing, and demolding High wear-resistant cement flower tiles are prepared by bricks, spray maintenance and other steps, and amino groups are introduced on the surface of graphene to enhance its binding force with cement.

Benefits of technology

It significantly improves the hardness and wear resistance of cement tiles, avoids cracks and easy wear problems, and meets the market's requirements for improving its decorative effect and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141364510000101
    Figure BDA0005141364510000101
  • Figure BDA0005141364510000111
    Figure BDA0005141364510000111
Patent Text Reader

Abstract

The invention relates to a high-wear-resistance cement tile and a preparation method thereof, and belongs to the technical field of cement tiles. The high-wear-resistance cement tile is prepared from white cement, ordinary cement, wear-resistant filler, oxidation pigment, quartz sand, fine sand, fine aggregate and albite, the mesh number of the albite is 250, and the preparation method of the high-wear-resistance cement tile comprises the steps of material preparation, mold feeding, grouting, mold drawing, material screening and brick pressing, demolding and brick taking and spraying maintenance. Amino groups (-NH2) are introduced on the surface of graphene to modify graphene, the amino groups have high reaction activity and can form chemical bonds with silicate ions (-SiO4) in cement, so that the binding force of graphene in the cement is enhanced, meanwhile, the amino groups are mixed with an emulsifier to obtain emulsion, and the dispersity of the emulsion in the cement is enhanced; in addition, when the quartz sand in the middle layer material and the albite in the bottom layer material are heated, the quartz sand and the albite react to generate sodium calcium silicate, so that the hardness and the wear resistance of the cement tile are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement tiles and relates to a high-wear-resistant cement tile and a preparation method thereof. Background Art

[0002] Cement tiles are a very common building decoration material in our daily life. They are a relatively special type of ceramic tile. The inherent simplicity and classical beauty of cement tiles attract more and more modern people, and are gradually being used in museums, cafes, cultural and creative parks and other places. With the continuous improvement of people's consumption level and aesthetic taste, the requirements for the decorative effect, pattern clarity, hardness, wear resistance, etc. of cement tiles are also gradually increasing. Cement tiles on the market usually have problems of cracks and easy wear. Therefore, the high wear-resistant cement tiles and the preparation method thereof provided by the present invention can effectively avoid the above problems. Summary of the invention

[0003] The present invention relates to a high wear-resistant cement tile and a preparation method thereof, and belongs to the technical field of cement tiles. The high wear-resistant cement tile disclosed in the present invention comprises the following raw materials: white cement, ordinary cement, wear-resistant filler, oxidized pigment, quartz sand, fine sand, fine aggregate, and albite, wherein the average mesh number of albite is 250 meshes, and the preparation method thereof comprises the following steps: material preparation, mold placement, grouting, mold extraction, material screening and brick pressing, demolding and brick taking, and spraying and curing. Amino groups (-NH2) are introduced on the surface of graphene to modify graphene, and the amino groups have high reactivity and can form chemical bonds with silicate ions (-SiO4) in cement, thereby enhancing the binding force of graphene in cement, and at the same time, they are mixed with an emulsifier to obtain an emulsion, thereby enhancing its dispersibility in cement; in addition, the quartz sand in the middle layer material and the albite in the bottom layer material react to form sodium silicate calcium salt when heated, thereby enhancing the hardness and wear resistance of the cement tile.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A high wear-resistant cement tile comprises the following raw materials: white cement, ordinary cement, wear-resistant filler, oxide pigment, quartz sand, fine sand, fine aggregate, and albite, wherein the average particle size of the albite is 150-300 meshes.

[0006] Furthermore, the preparation method of the highly wear-resistant cement tiles comprises the following steps:

[0007] (1) mixing the oxidized pigment and white cement, sieving the mixture, adding water and stirring to form a color paste for later use;

[0008] (2) mixing ordinary cement, fine sand, quartz sand and wear-resistant filler to obtain the middle layer material;

[0009] (3) Ordinary cement, fine aggregate, albite and wear-resistant filler are mixed to obtain a mixture a, and then water is added and stirred to obtain a base material;

[0010] (4) Clean and dry the mold, place the inner mold in the outer mold frame, inject the color paste and shake the entire mold to control the thickness of the color paste;

[0011] (5) Then pull out the inner mold, spread the middle layer material on the color paste, and use a scraper to smooth it;

[0012] (6) Finally, pour the bottom material into the outer mold, scrape it flat with a scraper, cover it with the bottom cover of the outer mold, and put it into the hydraulic press to press it into bricks;

[0013] (7) After demoulding and taking out the bricks, they are heated and placed after cooling to obtain cement tiles, and are sprayed with water for 3-7 consecutive days, with the surface of the cement tiles being wetted by spraying once a day.

[0014] Furthermore, in the step (1), the mass ratio of the oxidized pigment to the white cement is 1:15-25, the volume ratio of the mixture to water is 1:0.8-1.2, and the mesh size of the sieve is 150-200 meshes.

[0015] Furthermore, in step (2), the mass ratio of ordinary cement, fine sand, quartz sand and wear-resistant filler is 1:0.5:0.2-0.3:0.05-0.1.

[0016] Furthermore, in the step (3), the mass ratio of ordinary cement, fine aggregate, albite and wear-resistant filler is 1:1:0.2-0.3:0.1, and the volume ratio of the mixture a to water is 1:0.2-0.3.

[0017] Furthermore, the thickness of the color paste in step (4) is 3-3.5 mm, the volume ratio of the intermediate layer material to the color paste in step (5) is 1:0.4-0.5, and the amount of the bottom layer material poured into the step (6) is just enough to spread the entire outer mold, wherein the size of the outer mold is 22 cm×22 cm×3 cm, and the pressure of the hydraulic press is 8-10 MPa.

[0018] Furthermore, in the step (7), the heating temperature and time are 400-500° C. and 20-30 min respectively, and the standing time is 24-30 h.

[0019] Furthermore, the method for preparing the wear-resistant filler in step (2) and step (3) comprises the following steps:

[0020] A1: Graphene oxide powder and anhydrous ethanol are mixed and ultrasonicated for 1-2 hours, and then 3-aminopropyltriethoxysilane is added and stirred to form a mixture b;

[0021] A2: Mixture b is heated to reflux, and the obtained solid phase is washed 3-5 times with distilled water and dried to obtain modified graphene;

[0022] A3: Modified graphene is mixed with an emulsifier, heated, stirred and cut to obtain an emulsion, which is the wear-resistant filler.

[0023] Furthermore, in the step A1, the ratio of graphene oxide powder, anhydrous ethanol and 3-aminopropyltriethoxysilane is 1g:30mL:1mL, the heating reflux time in the step A2 is 3-4h, and the drying temperature and time are 100-110°C and 30-50min respectively.

[0024] Furthermore, in step A3, the ratio of modified graphene to emulsifier is 1-2g:3mL, wherein the emulsifier is composed of polyvinyl pyrrolidone, polyvinyl alcohol and distilled water in a mass ratio of 1:1-2:2, the heating refers to heating to 120-130°C, and the speed and time of stirring and pasting are 800-1000r / min and 10-20min respectively.

[0025] Beneficial effects of the present invention:

[0026] 1. Amino groups (-NH2) are introduced on the surface of graphene to modify graphene. Amino groups have high reactivity and can form chemical bonds with silicate ions (-SiO4) in cement, thereby enhancing the binding force of graphene in cement. At the same time, they are mixed with emulsifiers to obtain emulsions, which enhances its dispersibility in cement. Polyvinyl alcohol in the emulsifier has good water solubility and colloidal stability, and polyvinyl pyrrolidone has a long molecular chain that plays a role in blocking modified graphene. The combination of the two synergistically improves the dispersibility of modified graphene in cement.

[0027] 2. In addition, the quartz sand in the middle layer material and the albite in the bottom layer material react to form sodium calcium silicate when heated, which enhances the hardness and wear resistance of the cement tiles. DETAILED DESCRIPTION

[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0029] The white cement in all the embodiments and comparative examples of the present invention was purchased from McManee, the ordinary cement was purchased from Yinghua; the quartz sand was purchased from Pansheng; the graphene oxide powder was purchased from Jianshi; the quartz sand was purchased from Jilin Changyue Environmental Protection Equipment Co., Ltd.; the particle size of the fine sand was 0.25-0.35 mm; the fine aggregate was purchased from Anjian Hongye Construction Company; the model of polyvinyl pyrrolidone was K30; and the model of polyvinyl alcohol was CW40-705.

[0030] Example 1

[0031] A high wear-resistant cement tile comprises the following raw materials: white cement, ordinary cement, wear-resistant filler, oxide pigment, quartz sand, fine sand, fine aggregate, and albite, wherein the average particle size of the albite is 250 meshes.

[0032] The preparation method of the high wear-resistant cement tile comprises the following steps:

[0033] (1) mixing the oxidized pigment and white cement, sieving the mixture, adding water and stirring to form a color paste for later use;

[0034] (2) mixing ordinary cement, fine sand, quartz sand and wear-resistant filler to obtain the middle layer material;

[0035] (3) Ordinary cement, fine aggregate, albite and wear-resistant filler are mixed to obtain a mixture a, and then water is added and stirred to obtain a base material;

[0036] (4) Clean and dry the mold, place the inner mold in the outer mold frame, inject the color paste and shake the entire mold to control the thickness of the color paste;

[0037] (5) Then pull out the inner mold, spread the middle layer material on the color paste, and use a scraper to smooth it;

[0038] (6) Finally, pour the bottom material into the outer mold, scrape it flat with a scraper, cover it with the bottom cover of the outer mold, and put it into the hydraulic press to press it into bricks;

[0039] (7) After demoulding and taking out the bricks, they are heated and placed after cooling to obtain cement tiles, and are sprayed with water for 3 consecutive days, with water spraying once a day to wet the surface of the cement tiles.

[0040] In the step (1), the mass ratio of the oxidized pigment to the white cement is 1:20, the volume ratio of the mixture to water is 1:1, and the mesh size of the sieve is 150 meshes.

[0041] In the step (2), the mass ratio of ordinary cement, fine sand, quartz sand and wear-resistant filler is 1:0.5:0.2:0.05.

[0042] In the step (3), the mass ratio of ordinary cement, fine aggregate, albite and wear-resistant filler is 1:1:0.2:0.1, and the volume ratio of the mixture a and water is 1:0.2.

[0043] The thickness of the color paste in step (4) is 3 mm, the volume ratio of the intermediate layer material to the color paste in step (5) is 1:0.4, and the amount of the bottom layer material poured into the step (6) is just enough to cover the entire outer mold, wherein the size of the outer mold is 22 cm×22 cm×3 cm, and the pressure of the hydraulic press is 8 MPa.

[0044] The heating temperature and time in step (7) are 400° C. and 20 min respectively, and the standing time is 24 h.

[0045] The method for preparing the wear-resistant filler in step (2) and step (3) comprises the following steps:

[0046] A1: Graphene oxide powder was mixed with anhydrous ethanol and ultrasonicated for 1 h, and then 3-aminopropyltriethoxysilane was added and stirred to form a mixture b;

[0047] A2: Mixture b is heated to reflux, and the obtained solid phase is washed three times with distilled water and dried to obtain modified graphene;

[0048] A3: Modified graphene is mixed with an emulsifier, heated, stirred and cut to obtain an emulsion, which is the wear-resistant filler.

[0049] In the step A1, the ratio of graphene oxide powder, anhydrous ethanol and 3-aminopropyltriethoxysilane is 1g:30mL:1mL, the heating reflux time in the step A2 is 3h, and the drying temperature and time are 100°C and 30min respectively.

[0050] In the step A3, the ratio of modified graphene to emulsifier is 1g:3mL, wherein the emulsifier is composed of polyvinyl pyrrolidone, polyvinyl alcohol and distilled water in a mass ratio of 1:1:2, the heating refers to heating to 120°C, and the speed and time of stirring and pasting are 800r / min and 10min respectively.

[0051] Example 2

[0052] A high wear-resistant cement tile comprises the following raw materials: white cement, ordinary cement, wear-resistant filler, oxide pigment, quartz sand, fine sand, fine aggregate, and albite, wherein the average particle size of the albite is 250 meshes.

[0053] The preparation method of the high wear-resistant cement tile comprises the following steps:

[0054] (1) mixing the oxidized pigment and white cement, sieving the mixture, adding water and stirring to form a color paste for later use;

[0055] (2) mixing ordinary cement, fine sand, quartz sand and wear-resistant filler to obtain the middle layer material;

[0056] (3) Ordinary cement, fine aggregate, albite and wear-resistant filler are mixed to obtain a mixture a, and then water is added and stirred to obtain a base material;

[0057] (4) Clean and dry the mold, place the inner mold in the outer mold frame, inject the color paste and shake the entire mold to control the thickness of the color paste;

[0058] (5) Then pull out the inner mold, spread the middle layer material on the color paste, and use a scraper to smooth it;

[0059] (6) Finally, pour the bottom material into the outer mold, scrape it flat with a scraper, cover it with the bottom cover of the outer mold, and put it into the hydraulic press to press it into bricks;

[0060] (7) After demoulding and taking out the bricks, they are heated and placed after cooling to obtain cement tiles, and are sprayed with water for 5 consecutive days, with water spraying once a day to wet the surface of the cement tiles.

[0061] In the step (1), the mass ratio of the oxidized pigment to the white cement is 1:20, the volume ratio of the mixture to water is 1:1, and the mesh size of the sieve is 180 meshes.

[0062] In the step (2), the mass ratio of ordinary cement, fine sand, quartz sand and wear-resistant filler is 1:0.5:0.25:0.08.

[0063] In the step (3), the mass ratio of ordinary cement, fine aggregate, albite and wear-resistant filler is 1:1:0.25:0.1, and the volume ratio of the mixture a and water is 1:0.25.

[0064] The thickness of the color paste in step (4) is 3.2 mm, the volume ratio of the intermediate layer material to the color paste in step (5) is 1:0.45, and the amount of the bottom layer material poured into the step (6) is just enough to cover the entire outer mold, wherein the size of the outer mold is 22 cm×22 cm×3 cm, and the pressure of the hydraulic press is 9 MPa.

[0065] The heating temperature and time in step (7) are 450° C. and 25 min respectively, and the standing time is 26 h.

[0066] The method for preparing the wear-resistant filler in step (2) and step (3) comprises the following steps:

[0067] A1: Graphene oxide powder was mixed with anhydrous ethanol and ultrasonicated for 1.5 h, and then 3-aminopropyltriethoxysilane was added and stirred to form a mixture b;

[0068] A2: Mixture b is heated to reflux, and the obtained solid phase is washed 4 times with distilled water and dried to obtain modified graphene;

[0069] A3: Modified graphene is mixed with an emulsifier, heated, stirred and cut to obtain an emulsion, which is the wear-resistant filler.

[0070] In the step A1, the ratio of graphene oxide powder, anhydrous ethanol and 3-aminopropyltriethoxysilane is 1g:30mL:1mL, the heating reflux time in the step A2 is 3.5h, and the drying temperature and time are 105°C and 40min respectively.

[0071] In the step A3, the ratio of modified graphene to emulsifier is 1.5g:3mL, wherein the emulsifier is composed of polyvinyl pyrrolidone, polyvinyl alcohol and distilled water in a mass ratio of 1:1.5:2, the heating refers to heating to 125°C, and the speed and time of stirring and pasting are 900r / min and 15min respectively.

[0072] Example 3

[0073] A high wear-resistant cement tile comprises the following raw materials: white cement, ordinary cement, wear-resistant filler, oxide pigment, quartz sand, fine sand, fine aggregate, and albite, wherein the average particle size of the albite is 250 meshes.

[0074] The preparation method of the high wear-resistant cement tile comprises the following steps:

[0075] (1) mixing the oxidized pigment and white cement, sieving the mixture, adding water and stirring to form a color paste for later use;

[0076] (2) mixing ordinary cement, fine sand, quartz sand and wear-resistant filler to obtain the middle layer material;

[0077] (3) Ordinary cement, fine aggregate, albite and wear-resistant filler are mixed to obtain a mixture a, and then water is added and stirred to obtain a base material;

[0078] (4) Clean and dry the mold, place the inner mold in the outer mold frame, inject the color paste and shake the entire mold to control the thickness of the color paste;

[0079] (5) Then pull out the inner mold, spread the middle layer material on the color paste, and use a scraper to smooth it;

[0080] (6) Finally, pour the bottom material into the outer mold, scrape it flat with a scraper, cover it with the bottom cover of the outer mold, and put it into the hydraulic press to press it into bricks;

[0081] (7) After demoulding and taking out the bricks, they are heated and placed after cooling to obtain cement tiles, and are sprayed with water for 7 consecutive days, with water spraying once a day to wet the surface of the cement tiles.

[0082] In the step (1), the mass ratio of the oxidized pigment to the white cement is 1:20, the volume ratio of the mixture to water is 1:1, and the mesh size of the sieve is 200 meshes.

[0083] In the step (2), the mass ratio of ordinary cement, fine sand, quartz sand and wear-resistant filler is 1:0.5:0.3:0.1.

[0084] In the step (3), the mass ratio of ordinary cement, fine aggregate, albite and wear-resistant filler is 1:1:0.3:0.1, and the volume ratio of the mixture a and water is 1:0.3.

[0085] The thickness of the color paste in step (4) is 3.5 mm, the volume ratio of the intermediate layer material to the color paste in step (5) is 1:0.5, and the amount of the bottom layer material poured into the step (6) is just enough to cover the entire outer mold, wherein the size of the outer mold is 22 cm×22 cm×3 cm, and the pressure of the hydraulic press is 10 MPa.

[0086] The heating temperature and time in step (7) are 500° C. and 30 min respectively, and the standing time is 30 h.

[0087] The method for preparing the wear-resistant filler in step (2) and step (3) comprises the following steps:

[0088] A1: Graphene oxide powder was mixed with anhydrous ethanol and ultrasonicated for 2 h, and then 3-aminopropyltriethoxysilane was added and stirred to form a mixture b;

[0089] A2: Mixture b is heated to reflux, and the obtained solid phase is washed 5 times with distilled water and dried to obtain modified graphene;

[0090] A3: Modified graphene is mixed with an emulsifier, heated, stirred and cut to obtain an emulsion, which is the wear-resistant filler.

[0091] In the step A1, the ratio of graphene oxide powder, anhydrous ethanol and 3-aminopropyltriethoxysilane is 1g:30mL:1mL, the heating reflux time in the step A2 is 4h, and the drying temperature and time are 110°C and 50min respectively.

[0092] In the step A3, the ratio of modified graphene to emulsifier is 2g:3mL, wherein the emulsifier is composed of polyvinyl pyrrolidone, polyvinyl alcohol and distilled water in a mass ratio of 1:2:2, the heating refers to heating to 130°C, and the speed and time of stirring and pasting are 1000r / min and 20min respectively.

[0093] Comparative Example 1

[0094] On the basis of Example 2, the wear-resistant filler in step (2) is removed, and other conditions are consistent with Example 2.

[0095] Comparative Example 2

[0096] On the basis of Example 2, the wear-resistant filler in step (3) is removed, and other conditions are consistent with Example 2.

[0097] Comparative Example 3

[0098] On the basis of Example 2, step A1 and step A2 in the method for preparing the wear-resistant filler are removed, and the modified graphene in step A3 is replaced by graphene of equal mass, and other conditions are consistent with Example 2.

[0099] Comparative Example 4

[0100] On the basis of Example 2, the polyvinyl pyrrolidone in the emulsifier was removed and an equal mass of polyvinyl alcohol was used. Other conditions were consistent with those in Example 2.

[0101] Comparative Example 5

[0102] On the basis of Example 2, the polyvinyl alcohol in the emulsifier was removed and an equal mass of polyvinyl pyrrolidone was used. Other conditions were consistent with those in Example 2.

[0103] Comparative Example 6

[0104] On the basis of Example 2, the quartz sand in step (2) was removed, and the other conditions were consistent with Example 2.

[0105] Comparative Example 7

[0106] On the basis of Example 2, the albite in step (3) was removed, and the other conditions were the same as those in Example 2.

[0107] 1. Performance Testing

[0108] Wear resistance determination: According to the "Test Method for Wear Resistance of Inorganic Floor Materials" (GB / T12988-2009), the cement tiles prepared in Examples 1-3 and Comparative Examples 1-5 were tested for wear resistance. In addition, the cement colored tiles purchased on the market, which were purchased from Lehong, were tested together as a control group. The wear rates of the cement colored tiles and cement colored tiles after 30 minutes were calculated. The specific formula is:

[0109] Wear rate = (ab) / a×100%, where a is the mass of the tile before the test and b is the mass after the test;

[0110] Flexural strength test: The flexural strength test was performed on the cement tiles obtained in Examples 1-3 and Comparative Examples 6-7 and the control group according to the flexural strength of Jc410-91 cement tiles.

[0111] The above test results are shown in Table 1.

[0112] Table 1 Test results

[0113]

[0114]

[0115] It can be concluded from Table 1 that the wear rate of Examples 1-3 is lower than that of Comparative Examples 1-5 and the control group, while the flexural strength is higher than that of Comparative Examples 6-7 and the control group. No wear-resistant filler was added in Comparative Example 1-2, and its wear resistance decreased; Comparative Example 3 used modified graphene, and its bonding with cement decreased, thereby affecting wear resistance; the emulsifiers in Comparative Examples 4-5 were relatively single, and their dispersion effect was not ideal, which made the wear resistance effect worse; Comparative Examples 6-7 lacked quartz sand in the middle layer material or albite in the bottom layer material, and no sodium silicate calcium salt was generated, so the bonding between the layers decreased, and the flexural strength was greatly reduced.

[0116] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A highly wear-resistant cement tile, characterized in that: The high wear-resistant cement tiles include the following raw materials: white cement, ordinary cement, wear-resistant filler, oxidized pigment, quartz sand, fine sand, fine aggregate, and albite, wherein the average particle size of the albite is 150-300 meshes.

2. A highly wear-resistant cement tile according to claim 1, characterized in that: The preparation method of the high wear-resistant cement tile comprises the following steps: (1) mixing the oxidized pigment and white cement, sieving the mixture, adding water and stirring to form a color paste for later use; (2) mixing ordinary cement, fine sand, quartz sand and wear-resistant filler to obtain the middle layer material; (3) Ordinary cement, fine aggregate, albite and wear-resistant filler are mixed to obtain a mixture a, and then water is added and stirred to obtain a base material; (4) Clean and dry the mold, place the inner mold in the outer mold frame, inject the color paste and shake the entire mold to control the thickness of the color paste; (5) Then pull out the inner mold, spread the middle layer material on the color paste, and use a scraper to smooth it; (6) Finally, pour the bottom material into the outer mold, scrape it flat with a scraper, cover it with the bottom cover of the outer mold, and put it into the hydraulic press to press it into bricks; (7) After demoulding and taking out the bricks, they are heated and placed after cooling to obtain cement tiles, and are sprayed with water for 3-7 consecutive days, with the surface of the cement tiles being wetted by spraying once a day.

3. A highly wear-resistant cement tile according to claim 2, characterized in that: In the step (1), the mass ratio of the oxidized pigment to the white cement is 1:15-25, the volume ratio of the mixture to water is 1:0.8-1.2, and the mesh size of the sieve is 150-200 meshes.

4. The high wear-resistant cement tile according to claim 2, characterized in that: In the step (2), the mass ratio of ordinary cement, fine sand, quartz sand and wear-resistant filler is 1:0.5:0.2-0.3:0.05-0.

1.

5. The high wear-resistant cement tile according to claim 2, characterized in that: In the step (3), the mass ratio of ordinary cement, fine aggregate, albite and wear-resistant filler is 1:1:0.2-0.3:0.1, and the volume ratio of the mixture a and water is 1:0.2-0.

3.

6. The high wear-resistant cement tile according to claim 2, characterized in that: The thickness of the color paste in step (4) is 3-3.5 mm, the volume ratio of the intermediate layer material to the color paste in step (5) is 1:0.4-0.5, the amount of the bottom layer material poured into the step (6) is just enough to spread the entire outer mold, and the pressure of the hydraulic press is 8-10 MPa.

7. The high wear-resistant cement tile according to claim 2, characterized in that: The heating temperature and time in step (7) are 400-500° C. and 20-30 min respectively, and the standing time is 24-30 h.

8. The high wear-resistant cement tile according to claim 2, characterized in that: The method for preparing the wear-resistant filler in step (2) and step (3) comprises the following steps: A1: Graphene oxide powder and anhydrous ethanol are mixed and ultrasonicated for 1-2 hours, and then 3-aminopropyltriethoxysilane is added and stirred to form a mixture b; A2: Mixture b is heated to reflux, and the obtained solid phase is washed 3-5 times with distilled water and dried to obtain modified graphene; A3: Modified graphene is mixed with an emulsifier, heated, stirred and cut to obtain an emulsion, which is the wear-resistant filler.

9. The high wear-resistant cement tile according to claim 8, characterized in that: In the step A1, the ratio of graphene oxide powder, anhydrous ethanol and 3-aminopropyltriethoxysilane is 1g:30mL:1mL, the heating reflux time in the step A2 is 3-4h, and the drying temperature and time are 100-110°C and 30-50min respectively.

10. The high wear-resistant cement tile according to claim 8, characterized in that: In the step A3, the ratio of modified graphene to emulsifier is 1-2g:3mL, wherein the emulsifier is composed of polyvinyl pyrrolidone, polyvinyl alcohol and distilled water in a mass ratio of 1:1-2:2, the heating refers to heating to 120-130°C, and the speed and time of stirring and pasting are 800-1000r / min and 10-20min respectively.

Citation Information

Patent Citations

  • Prefabricated terrazzo tile with riffled pattern

    CN1058167A

  • High-strength pavement brick and preparation method thereof

    CN107857568A

  • Preparation method of toughened thermal insulation tile

    CN108178558A

  • Manufacturing method of high-intensity water holding type grass-planting brick

    CN108503284A

  • Composite sponge containing amino-modified graphene, preparation method and uses thereof

    CN110193358A